Modelo de integração entre a universidade e o ensino fundamental baseado em fluxo de conhecimento - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2017)
Education, in a global scale, is facing a period of deep changes. In this country, changes are directed connected with weak indicators found in analysis and evaluations performed by the government. In this context, this thesis targets the application of theories (Constructivism and Constructionism) and related concepts (Design Thinking for Educators and Maker for Education) aiming at generating knowledge about the integration of two distant worlds, namely the university and the primary school, based on the exchange of knowledge sources. Aiming at to bridge those two worlds, this work caracterizes the existing distance and some problems that justify this distance. Roots supporting this research are shown and discussed, specially a good literature review of main areas involved in this work. The model supporting the integration between university - primary school is then presented and discussed, together with the assessment methodology devised to explore and validate the work. The research methodology adopted here is action-research, since it combines action and solution of a given problem, trough an interactive process. Main results produced by this thesis include the conceptual model supporting the bridge, some scientific papers, several technological products, the supervision of academic works, and more. Open points and the main challenges still remaining are also discussed here.
Keywords: Construtivismo; Construcionismo; Design Thinking for Educators; Maker for Education; Conhecimento; Aprender Fazendo; CNPQ::CIÊNCIAS HUMANAS; GESTÃO DO CONHECIMENTO E INOVAÇÃO TECNOLÓGICA PARA O DESENVOLVIMENTO SUSTENTÁVEL